The Dimension of Textile use in the Expression of Verbal Creativity - Ilona Valantinaite; Zivile Sedereviciute-Paciauskiene (European Scientific Journal, ESJ, 2022)
The article investigates the Baltic pre-service Technology teachers' expression of verbal creativity in their final years of study and analyzes the constituent dimension of sustainable textile consumption. The students' verbal creativity was examined using a verbal expression questionnaire compiled following the methodological recommendations of E. P. Torrance for diagnosing a person’s creativity. The development of sustainable textile consumption is part of the Technological education curriculum analyzing responsible consumption issues that are becoming more complex. In most cases, education directly depends on the educator's knowledge, skills, values, habits, experience, and communication. The present research disclosed students – pre service teachers understanding that handicrafts are not related to ethnicity, values, or a phenomenon, which calls for exceptional protection. The integral model of tasks on identification/development of verbal creativity expression and identification/development of sustainable textile consumption was presented in the article.